Crusoe, Friday and the Raced Market Frame of Orthodox Economics Textbooks. Issue 5 (3rd September 2018) - Watson, Matthew
ABSTRACT: 'Crusoe' and 'Friday' signifiers necessarily evoke a world of racialised hierarchies. Economics textbooks are perhaps the sole remaining medium to simply wish away their resulting relations of power. These are the teaching aids that inspire students analytically to think of markets as pristine economic institutions and persuade them politically that they should want to will such institutions into being. Yet they all-too-often rely on the pedagogical device of the so-called Robinson Crusoe Economy, where the main characters from Defoe's most famous novel are required to instinctively recognise their equality within voluntary contracting agreements so that each can act as the neoclassical homo economicus. In other words, economists' Crusoe and Friday figures must behave antithetically to what has historically been implied by the 'Crusoe' and 'Friday' signifiers. But how can this be so, given how commonplace it was when Defoe's characters were first introduced into economic theory in the 1850s to justify white settler colonialism on the grounds that 'savage' societies lacked the capacity to be self-governing? The raced market frame that emerged in practice from this assumption continues to be reproduced uncritically today by Crusoe's and Friday's presence in the textbook explanation of the most basic model of market exchange.